Diagnosis and therapeutic strategies for primary bladder mucinous adenocarcinoma: a case report and literature review - Cheng, Xi; Wang, Weibo; Yang, Lexing; Tai, Supeng; Tao, Junyue; Fu, Yao; Zhou, Jun (Frontiers in Oncology, 2025)
Primary bladder mucinous adenocarcinoma (BMA) is an exceedingly rare and aggressive malignancy. We report a case of a 72-year-old male presenting with hematuria and dysuria. Imaging revealed a bladder mass, and histopathological examination following biopsy demonstrated characteristic extracellular mucin pools and signet-ring cells. Immunohistochemistry (IHC) was crucial for diagnosis, showing a negative profile for GATA binding protein 3 (GATA3) and Special AT-rich sequence-binding protein 2 (SATB2), along with membrane nuclear positivity for β-catenin. Endoscopic examination confirmed the absence of a primary gastrointestinal malignancy. The patient underwent robot-assisted laparoscopic radical cystoprostatectomy followed by three cycles of adjuvant chemotherapy with the FOLFOX regimen (5-fluorouracil, leucovorin, and oxaliplatin). No recurrence was observed during the 6-month follow-up. This case highlights the diagnostic challenges of BMA and emphasizes the importance of a multimodal diagnostic approach incorporating histopathology, immunohistochemistry, and endoscopy. The potential efficacy of adjuvant FOLFOX regimen is worth further exploration given the lack of standard therapeutic guidelines for this rare entity.